William Luther Pierce’s The Turner Diaries on Neo-Nazi Violence Language Usage in Social Media Propaganda “Unite The Right” Rally - Yesaya Parasian Pratama (Rubikon : Journal of Transnational American Studies, 2023)
The US has a long history of revolution where the ideological and cultural systems are deep rooted in the people. Apart from its democratic system, the country is also full of conservative ideology of racism, where one of them is Neo Nazi. This article employs in-depth method using Structural-Functional Approach to describing how neo-Nazi compiling their power as a group, Critical Discourse Analysis to analyze how William Luther Pierce’s The Turner Diaries can make impact of the movement, and Neo-Nazi as a white supremacy ideology based on post-nationalism concept showed that the similar norms and perspective in different countries can lead to unity and integration as well as omit borders from Germany to the United States. Moreover, factors of language and government system can also intensify of the method result.  From the confederation and The Turner Diaries, the ideas of white supremacy were disseminated and manifested through the parade and Jason Kessler’s propaganda in social media towards the campaign of anti-Jewish, Asian, and black people. All the factors matter for the neo-Nazi movement to run the rally and the fuel for defending their identity.